Ginkgo biloba attenuates complete Freund’s adjuvant-induced inflammatory pain by suppressing the NF-κB-CXCL1/CXCR2 signaling cascade in the rat spinal cord - Sherine Abdel Salam; Catherine S. George; Najla K. Al Abdulsalam; Ashraf M. Abdel-Moneim; Amina E. Essawy (Redox Report)
Background: Inflammatory pain is the most common type of chronic pain, and it is rapidly becoming a global health problem. Ginkgo biloba (EGb761) is a natural plant that contains several bioactive components with antioxidant and free radical scavenging properties. However, its underlying mechanism in inflammatory pain remains unclear. The aim of this study was to assess the effects and mechanisms of EGb761 on a complete Freund’s adjuvant (CFA)-induced inflammatory pain model in rats.Methods: A single dose of CFA was subcutaneously injected into the right hind paws of the rats, after which EGb761 (100 mg/kg/day) was orally administered for 14 days.Results: Oral EGb761 markedly decreased hind paw edema in CFA-treated rats. In addition, EGb761 significantly reduced thermal hyperalgesia by increasing the hot plate latency and improved motor coordination. Notably, EGb761 significantly reduced nitric oxide levels and catalase enzyme activity in the lumbar spinal cord (LSPC) of CFA-treated rats. Furthermore, EGb761 inhibited the mRNA expression of NF-ĸB, CXCL1, and CXCR2. At the histological level, EGb761 prevented CFA-induced tissue and neuronal damage in the LSPC dorsal horn. The immunohistochemical analysis revealed that caspase-3 levels were significantly reduced, whereas Bcl-2 expression was insignificantly increased with EGb761 treatment in rats with CFA-induced inflammation.Conclusion: EGb761 alleviated CFA-induced chronic inflammatory pain by attenuating oxidant–antioxidant dysregulation, blocking the NF-κB-CXCL1/CXCR2 inflammatory axis, and counteracting neural cell apoptosis in the LSPC. Our results suggest that EGb761 can be used as an analgesic for the treatment of pain associated with inflammation and tissue injury.